2015
DOI: 10.1021/acs.jpca.5b05368
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Aggregation of Molecules on Ice Nanoparticles

Abstract: Multiple molecules adsorbed on the surface of nanosized ice particles can either remain isolated or form aggregates, depending on their mobility. Such (non)aggregation may subsequently drive the outcome of chemical reactions that play an important role in atmospheric chemistry or astrochemistry. We present a molecular beam experiment in which the controlled number of guest molecules is deposited on the water and argon nanoparticles in a pickup chamber and their aggregation is studied mass spectrometrically. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(55 citation statements)
references
References 51 publications
9
46
0
Order By: Relevance
“…The first is a cluster beam (CLUB) apparatus located in Prague, Czech Republic [ 12 , 15 ]. The clusters were produced by a supersonic expansion into vacuum, and the beam was skimmed and passed through three differentially pumped chambers (one containing a pickup cell) into an interaction chamber where it was crossed with an electron beam of variable energy.…”
Section: Methodsmentioning
confidence: 99%
“…The first is a cluster beam (CLUB) apparatus located in Prague, Czech Republic [ 12 , 15 ]. The clusters were produced by a supersonic expansion into vacuum, and the beam was skimmed and passed through three differentially pumped chambers (one containing a pickup cell) into an interaction chamber where it was crossed with an electron beam of variable energy.…”
Section: Methodsmentioning
confidence: 99%
“…A similar result was obtained later by Pysanenko et al considering CH 3 Cl molecules adsorbed on ice, who concluded that the interaction with the polar water molecules inhibits the mobility of the adsorbed molecules. 20 Moreover, it was also shown by means of metastable impact electron spectroscopy that CHCl 3 molecules are adsorbed at the ice surface with their H atom oriented towards the substrate below 120 K, 21 and for all chlorinated methane derivatives (CH 4-x Cl x ) that their interaction with water occurs through the oxygen atom. 22 Finally, Vysokikh et al…”
Section: Introductionmentioning
confidence: 99%
“…Aoki et al showed, using metastable impact electron spectroscopy that CH 3 Cl molecules adsorbed at the ice surface turn their H atoms towards the ice phase below 120 K [26]. It was also shown that both CHCl 3 [24,25] and CH 3 Cl [27] remain immobile at the ice surface in the entire temperature range below desorption due to their interaction with the surface water molecules [24,25,27], and that the interaction of all chlorinated methane derivatives with water involves the water O atom [28].…”
Section: Introductionmentioning
confidence: 99%